PENINGKATAN KUALITAS CAMPURAN KULIT PISANG DENGAN AMPAS TAHU MELALUI FERMENTASI DENGAN Phanerochaete chrysosporium DAN Neurospora crassa SEBAGAI PAKAN TERNAK - Nuraini Nuraini; Maria Endo Mahata; Ade Djulardi (State Islamic University of Sultan Syarif Kasim Riau, 2014)
Banana peel can be used as an alternative feed based on the potential availability and nutritional. The experiments were conducted to improve the nutrient quality of Banana Peel and Tofu Waste mixture (BPTW) by using Phanerochaete chrysosporium and Neurospora crassa. This substrate consists of banana peel 70% and tofu waste 30%. The experiment was performed in 3 treatment completely randomized design (CRD) with 6 replicates. The treatments were : A= fermentation BPTW by Phanerochaete chrysosporium and Neurospora crassa (1:1), B = fermentation BPTW by Phanerochaete chrysosporium and Neurospora crassa (2:1), and C = fermentation BPTW by Phanerochaete chrysosporium and Neurospora crassa (1:2). Measured variables were Crude Fiber (CF), Crude Protein (CP), Nitrogen Retention and CF digestion. The result of the research showed that the treatment affected significantly (p<0.01) reduced CF and increased CP, nitrogen retention and CF digestion. In conclusion, fermentation by Phanerochaete chrysosporium and Neurospora crassa (2:1) was the best treatment for improving banana peel and tofu waste nutrient quality